complete horse - Lang, Amanda; Constantino, maria (England D&s, 2006)
The book divided into tow sections - care and Breeds, the first section looks at all aspects of horses and pony care inclouding choosing a suituble horse, feeding, living accommodation, grooming, exercising, health care and learning to ride
A highly informative guide to the world of horse
Keywords: Horsemanship; Horses -- Breeding; Horses -- Training; Horses -- diseases